An electroluminescent and tunable cavity-enhanced carbon-nanotube-emitter in the telecom band - Ovvyan, Anna; Li, Min-Ken; Gehring, Helge; Beutel, Fabian; Kumar, Sandeep; Hennrich, Frank; Wei, Li; Chen, Yuan; Pyatkov, Felix; Krupke, Ralph; Pernice, Wolfram (Nature Communications, 2023)
Emerging photonic information processing systems require chip-level integration of controllable nanoscale light sources at telecommunication wavelengths. Currently, substantial challenges remain in the dynamic control of the sources, the low-loss integration into a photonic environment, and in the site-selective placement at desired positions on a chip. Here, we overcome these challenges using heterogeneous integration of electroluminescent (EL), semiconducting carbon nanotubes (sCNTs) into hybrid two dimensional - three dimensional (2D-3D) photonic circuits. We demonstrate enhanced spectral line shaping of the EL sCNT emission. By back-gating the sCNT-nanoemitter we achieve full electrical dynamic control of the EL sCNT emission with high on-off ratio and strong enhancement in the telecommunication band. Using nanographene as a low-loss material to electrically contact sCNT emitters directly within a photonic crystal cavity enables highly efficient EL coupling without compromising the optical quality of the cavity. Our versatile approach paves the way for controllable integrated photonic circuits.